Pronunciation Errors Committed by First Year English Students at Tadulako University - Agung Pranawijaya,; Sudarkam Mertosono,; Wahyudin, Wahyudin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The research investigates errors in the pronunciation of words containing fricative sound among first-year English education students at Tadulako University. The researcher utilized a quantitative descriptive design in this research. There were twenty five first year English department students participated in this research. The data analysis reveals 678 errors out of 1500 content, with a 45.2% error rate. The most dominant errors is identified in 'final' position with 66.2% error rate, it also revealed that consonant ‘ʒ’ is the most difficult sound to be pronounced by the students with 63.7% error rate.